Influence of anodization time on the surface modifications on α-Fe2O3 photoanode upon anodization. Issue 11 (19th February 2016) - Maabong, Kelebogile; Hu, Yelin; Braun, Artur; Machatine, Augusto G.J.; Diale, Mmantsae
Abstract: Abstract : In searching for a suitable semiconductor material for hydrogen production via photoelectrochemical water splitting, α-Fe2 O3 received significant attention as a promising photoanode due to its band gap (∼2.1 eV), good stability, low cost, and natural occurrence. α-Fe2 O3 thin films were prepared by economic and facile dip coating method and subsequently subjected to an anodic potential of 700 mV versus Ag/AgCl in 1M KOH for different anodization times (1, 10, and 900 min) under illumination. X-ray diffractometry revealed increase in crystallites size from ∼31 nm for nanoparticles in pristine state to ∼38 and 44 nm after anodization for 1 and 900 min, respectively. A clear positive correlation between anodization time and grain (particle) size was observed from field emission gun scanning electron microscopy and atomic force microscopy (AFM); longer exposure time to anodizing conditions resulted in larger grains. Grain size increased from ∼57.9 nm in pristine state to ∼153.5 nm after anodization for 900 min. A significant smoothening of the surface with increase in anodization time was evident from AFM analysis.